Performance assessment of a developed rolling mill - Chughiefe, Lucky; Ebunilo, Patrick Okechukwu; Orhorhoro, Ejiroghene Kelly; Erhinyodavwe, Onoriode (Penerbit Universiti Kebangsaan Malaysia, 2024)
Rolling of metals has found applications in automotive, construction, agriculture, railroads, housing, metal furniture making, home appliances, electronic cabinetry, pipes and tubing etc. These have as well contributed to human and environmental sustainability. Nevertheless, the applications of metal rolling processes and machines have not been adequately harnessed in our locality due to unavailability of the rolling machine in small scale industries, laboratories and workshops in institutions of learning in the region. Annealing heat treatment was carried out on a mild steel round bar of 50 mm diameter and length of 200 samples. The samples were charged into an SXL muffle furnace with an annealing temperature of 950oC. The mechanical properties and the microstructure of the rolled mild carbon steel were evaluated. The results of the performance evaluation of the machine through assessment of the metallurgical characteristics of the rolled products from the machine and assessment of mechanical properties such as tensile strength and hardness of the rolled products from the machine showed an increase in the tensile strength from 250.85 MPa to 258.85 MPa, an increase in the ultimate tensile strength from 535.88 MPa to 540.05 MPa, an increase in the hardness from 140 HV to 145 HV, and a decrease in the percentage ductility of the mild carbon steel from 56% to 51%. Also, the optical micrograph of the rolled samples shows a coarse microstructure of grain refinement from slipping and pilling of dislocations.